DETERMINANTS OF UKRAINE'S POPULATION HEALTH: ECOLOGICAL MEASUREMENT (Regional aspects of productive forces development of Ukraine, 2019)
Based on the official statistics and the results of the author's sociological research, the current state of atmospheric air in Ukraine is estimated. By the method of logistic regression, the dependence between the state of health of the Ukrainian population (chances of having / not having a chronic disease) and the purity of atmospheric air is revealed. The main causes of death caused by air pollution are identified. Risks to public health related to environmental pollution have been identified, the degree of their adverse effects has been determined, incl. in the regional context. These ways of reducing the negative impact of air pollution.